Enviroscore: normalization, weighting, and categorization algorithm to evaluate the relative environmental impact of food and drink products - Saioa Ramos; Lucia Segovia; Angela Melado-Herreros; Maite Cidad; Jaime Zufía; Liesbet Vranken; Christophe Matthys (npj Science of Food, 2022)
Abstract A 5-scale label that relativizes the environmental impact of a given product referred to the impact of the European food basket is proposed. It was developed based on the Product Environmental Footprint methodology with the following stepwise approach. First, a set of normalization and weighting factors were defined to aggregate all the environmental impact categories into a single dimensionless index referred to as the European food basket, coined the European Food Environmental Footprint Single Index (EFSI). Next, the effectiveness of the EFSI index was evaluated by assessing the distribution of the EFSI results on 149 hypothetical food items and comparing it with the results obtained with EC Single Score. Finally, the thresholds to translate the EFSI index into the 5-scale Enviroscore (A, B, C, D, and E) were established and validated using the Delphi method. Results indicated that both, Enviroscore and EFSI, were able to account for impact variability between and within food products. Differences on the final score were observed due to the type of products (vegetables vs. animal products), the country of origin and the mean of transportation. Regarding country of origin, results indicated that differences in water stress impact category were better captured by the EFSI index (r = 0.624) than by the EC Single Score (r = 0.228). Finally, good agreement achieved with the Delphi method (weighted Kappa 0.642; p = 0.0025), ensures the acceptability of the Enviroscore. In conclusion, this study developed a method to communicate environmental impact assessment in a front-of-packaging label.